(untitled) (Studia Prawnicze / The Legal Studies, 2002)
Nowelizacja art. 448 wyłącza, moim zdaniem, możliwość kumulacji roszczeń z art. 445 i 448 k.c. Na pierwszy plan wysuwa się tu kompensacyjna funkcja omawianych przepisów. Opierając się na brzmieniu art. 77 Konstytucji, należy opowiedzieć się za modelem ochrony dóbr osobistych, bazującym na przesłance bezprawności jako warunku przypisania odpowiedzialności za naruszenie dóbr osobistych przez Państwo i ponadto potraktować tę normę jako pewien postulat zmiany zasad odpowiedzialności za naruszenie dóbr osobistych w ogóle. Skoro konstytucja zrównuje podmioty według kryterium własności, ta za sprzeczne z nią można by uznać przepisy, które podmioty własności państwowej obciążają odpowiedzialnością ostrzejszą niż podmioty niepubliczne. Zjawisko ekspansji teorii zakładających obiektywizację odpowiedzialności cywilnej i tym samym uniezależnienie jej od winy sprawcy, przy "współudziale" rozwoju instytucji ubezpieczeń pozwala postawić tezę, iż na wzorze modelu odpowiedzialności z art. 77 Konstytucji opierać się będzie w przyszłości cały gmach odpowiedzialności odszkodowawczej. Za przejaw tej ogólnie występującej tendencji uznaję odpowiedzialność za naruszenie dóbr osobistych. Konieczność obiektywizacji odpowiedzialności osób prawnych powinna dotyczyć także odpowiedzialności Skarbu Państwa za szkody wyrządzone poza zakresem imperium; ma to swoje podłoże w konstytucyjnym zrównaniu podmiotów według kryterium własnościowego. Interes majątkowy nigdy nie może zostać postawiony przez prawo wyżej od niemajątkowego - osobistego. Wynika to z zasad współżycia społecznego. To, że sprawca szkody majątkowej nie ponosi za nią odpowiedzialności, absolutnie nie powinno zwalniać z obowiązku pokrycia szkody niemajątkowej, oczywiście przy zaistnieniu przesłanki bezprawności jego działania. Dobrym przykładem relacji praw osobistych i praw majątkowych jest treść art. 142 k.c., stawiającego własność, a więc najpełniejsze prawo majątkowe, poniżej praw związanych z istotą ludzką. Nieuzasadnione jest różnicowanie siły ochrony dóbr osobistych w jej aspekcie niemajątkowym i majątkowym. Taka sytuacja była uzasadniona przed nowelizacją art. 448, gdy naruszenie dóbr nie było traktowane (z wyjątkiem dóbr wymienionych w art. 445) jako podstawa domagania się przez pokrzywdzonego zadośćuczynienia. Nie można oprzeć powództwa o naprawienie szkody niemajątkowej na art. 448, jeżeli dotyczy uszkodzenia ciała lub rozstroju zdrowia. Wyłączną podstawą takich roszczeń jest art. 445 k.c. W innym wypadku należałoby uznać ten ostatni przepis za zbędny, co stoi w sprzeczności z założeniem racjonalnego ustawodawcy. Dobra osobiste nie są kategorią jednorodną wewnętrznie i podlegają wartościowaniu na podstawie ich miejsca w życiu społecznym. "Niżej cenione" dobra chroni art. 448. Odpowiedzialność z art. 445 k.c. również bazuje na przesłance bezprawności naruszenia integralności cielesnej czy seksualnej lub prawa do wolności. Przepisy działu o czynach niedozwolonych nie zawierają bowiem norm jednorodnych tematycznie, a wobec zmiany treści art. 448 nie sposób zaakceptować utrzymania art. 445 bez zaniechania dotychczasowego rozumienia zawartych w tym przepisie norm. Omawiane przepisy art. 445 i 448 znajdują się wśród przepisów normujących warunki, jakim ma odpowiadać naprawienie szkody, będąc rozwinięciem odpowiednich postanowień art. 24 i 361 k.c., a nie art. 415. Charakter odpowiedzialności pozostał ten sam również po nowelizacji kodeksu cywilnego. Stanowisko to jest nie tylko konsekwencją faktu, iż odpowiedzialność sprawcza jest podstawowym modelem zawartym w k.c. Odpowiedzialność sprawcza z art. 448 k.c. ma źródło w niezwykle ścisłym powiązaniu odpowiedzialności z tego przepisu z art. 24 k.c., przewidującym odpowiedzialność sprawcy naruszenia dobra osobistego. Różnice między zdolnością deliktową a zdolnością w zakresie naruszenia dóbr osobistych są na tyle znaczne (w zw. z brzmieniem art. 24 § 1 k.c.), iż odpowiedzialność osoby prawnej należy ograniczyć do przypadków odpowiedzialności sprawczej za czyn własny. W pozostałym zakresie za naruszenie dóbr osobistych przez osobę np. podlegającą kierownictwu osoby prawnej odpowiedzialność poniesie sam podwładny - sprawca naruszenia dóbr osobistych i szkody niemajątkowej. Założenie przeciwne byłoby nazbyt represyjne względem osób prawnych, będących kategorią niejednorodną wewnętrznie i przez to nie zawsze zdolną do ponoszenia ryzyka surowej odpowiedzialności. Dobra osobiste są w stanie naruszyć jedynie osoby: prawne i fizyczne. Zgodnie zaś z obowiązującą teorią reprezentacji jedynie zachowanie się organów (osób fizycznych pełniących funkcje organu) poczytuje się za zachowanie się samej osoby prawnej. W ten sposób, nie negując sprawczego charakteru odpowiedzialności z art. 448 k.c., uzyskuje się wskazówkę praktyczną w przypadkach, gdy pozwanym o zapłatę zadośćuczynienia jest osoba prawna. Postanowienie art. 448 k.c. odnosi się wprost do procesu, konkretnie zaś do orzekania o obowiązku naprawienia szkody. Wynika to stąd, iż ścisłe udowodnienie wysokości szkody niemajątkowej jest wykluczone przez sam niematerialny charakter uszczerbku. Konstrukcja adekwatnego związku przyczynowego nie sprzeciwia się, moim zdaniem, przyjęciu ryzyka sprawcy co do szczególnych cech poszkodowanego, a wręcz można uznać, iż sprawca poniósłby surowszą odpowiedzialność, gdyż pomiędzy jego zachowaniem a szkodą istniałby niewątpliwy związek adekwatny. Normalnym bowiem następstwem kopnięcia człowieka o kruchych kościach jest złamanie kości. Rozważania te, aktualne głównie w odniesieniu do art. 445 k.c., nie będą odnosić się do ochrony osób prawnych, które ze swej natury nie mają szczególnych cech modyfikujących odpowiedzialność sprawcy. Do powstania prawa do zadośćuczynienia konieczne jest, by naruszenie dóbr osobistych spowodowało wystąpienie szkody niemajątkowej. Nie istnieje w powyższym zakresie żadne domniemanie szkody niemajątkowej. Powód musi udowodnić istnienie uszczerbku oraz jego wysokość. Ponieważ często jest to niemożliwe, kodeks pozostawia sądowi pewną swobodę w postaci możności zasądzenia odpowiedniej kwoty. Oznacza to, iż sąd, biorąc pod uwagę wszelkie okoliczności sprawy, orzeka o wysokości zadośćuczynienia. The amendment to Article 448 excludes, in my view, the possibility of cumulation of claims under Articles 445 and 448 of the Civil Code. The compensatory function of the provisions in question comes to the fore here. Based on the wording of Article 77 of the Constitution, it is necessary to advocate a model of personal property protection based on the premise of unlawfulness as a condition for the attribution of liability for the violation of personal property by the State and, moreover, to treat this norm as a certain postulate for a change in the principles of liability for the violation of personal property in general. Since the constitution equates entities according to the criterion of ownership, this one could be seen as contradictory to the constitution, which holds State-owned entities more severely liable than non-public entities. The phenomenon of the expansion of theories assuming the objectivisation of civil liability and thus making it independent of the perpetrator’s fault, with the ’complicity’ of the development of insurance institutions, allows one to put forward a thesis that the whole edifice of liability for damages will, in the future, be based on the model of liability from Article 77 of the Constitution. I consider liability for infringement of personal rights to be a manifestation of this generally occurring trend. The need to objectivise the liability of legal persons should also apply to the liability of the State Treasury for damage caused outside the scope of the imperium; this is rooted in the constitutional equation of subjects according to the ownership criterion. The law must never place the pecuniary interest over the non-pecuniary and personal one. This is due to the principles of comity. The fact that the perpetrator of the pecuniary damage is not responsible for it should absolutely not absolve the obligation to pay for the non-pecuniary damage, of course under the premise of the unlawfulness of his action. A good example of the relationship between personal rights and property rights is Article 142 of the Civil Code, which places property, i.e. the fullest property right, below the rights associated with the human being. It is unreasonable to differentiate between the strength of the protection of personal rights in its non-property and property aspects. Such a situation was justified before the amendment of Article 448, when the violation of goods was not treated (with the exception of those listed in Article 445) as a basis for the victim to claim punitive damages. An action for non-pecuniary damage cannot be based on Article 448 if it relates to bodily injury or disorder of health. The exclusive basis for such claims is Article 445 of the Civil Code. Otherwise, the latter provision would have to be regarded as superfluous, which contradicts the assumption of a rational legislator. Personal property is not an internally homogeneous category and is subject to value based on its place in social life. ‘Inferior goods’ are protected by Article 448. Liability under Article 445 of CC is also based on the premise of unlawfulness of the violation of bodily or sexual integrity or the right to liberty. Indeed, the provisions of the section on torts do not contain thematically homogeneous norms and, in view of the amendment of Article 448, it is unacceptable to maintain Article 445 without abandoning the existing understanding of the norms contained in this provision. The provisions in question, Articles 445 and 448, are among the provisions that regulate the conditions to which compensation for damage is to correspond, being a development of the relevant provisions of Articles 24 and 361 of the Civil Code, rather than Article 415. The nature of liability remained the same even after the amendment of the Civil Code. This position is not only a consequence of the fact that causal liability is the basic model contained in the Civil Code. The causal liability under Article 448 of the Civil Code is rooted in the extremely close connection between liability under this provision and Article 24 of the Civil Code, which provides for the liability of the perpetrator of the infringement of a personal good. The differences between capacity in tort and capacity in respect of infringement of personal rights are so significant (in connection with the wording of Article 24 § 1 of CC) that the liability of a legal person should be limited to cases of causal liability for an own act. Otherwise, the subordinate himself - the perpetrator of the violation of personal rights and non-pecuniary damage - will be liable for the violation of personal rights by a person, e.g. subject to the management of a legal entity. An assumption to the contrary would be overly repressive towards legal persons, which are an internally heterogeneous category and thus not always capable of bearing the risk of strict liability. Personal rights are only capable of being infringed by persons: legal and natural. On the other hand, according to the current theory of representation, only the behaviour of the corporate bodies (natural persons acting as an corporate body) is deemed to be the behaviour of the legal person itself. Thus, without denying the causal nature of liability under Article 448 of CC, a practical guideline is obtained in cases where the defendant for punitive damages is a legal person. The provision of Article 448 of CC refers explicitly to the trial, specifically to the adjudication of the obligation to compensate for damage. This is because strict proof of the amount of non-pecuniary damage is precluded by the intangible nature of the damage itself. The construction of an adequate causal relationship does not, in my opinion, contradict the assumption of the perpetrator’s risk as to the specific characteristics of the injured party, and indeed it could be argued that the perpetrator would be held more severely liable, as there would be an undoubtedly adequate link between his conduct and the damage. This is because the normal consequence of kicking a man with fragile bones is a broken bone. These considerations, which are mainly valid in relation to Article 445 of the Civil Code, will not apply to the protection of legal persons, which by their nature do not have specific features modifying the liability of the perpetrator. In order for the right to punitive damages to arise, it is necessary that the infringement of personal rights has caused non-pecuniary damage. There is no presumption of non-pecuniary damage in the above regard. The claimant must prove the existence of the injury and its amount. As this is often not possible, the Code leaves the court some leeway in the form of being able to award an appropriate amount. This means that the court will take into account all the circumstances of the case and then decide on the amount of punitive damages.